Integrative Non-Pharmacological Interventions for Anxiety Management in Chemotherapy Patients: A Systematic Review - Arif Imam Hidayat; Agis Taufik; Galih Noor Alivian; Triyanto Triyanto (Journal of Bionursing, 2026)
Abstract Background: Anxiety is a prevalent and debilitating symptom among cancer patients undergoing chemotherapy. Pharmacological anxiolytics can produce undesirable side‑effects and may interact with cancer treatments. Consequently, research has explored non‑pharmacological interventions—such as mindfulness‑based interventions, cognitive–behavioural and acceptance therapies, relaxation practices, and complementary modalities—to reduce anxiety. This review critically evaluates randomized controlled trials (RCTs) and systematic reviews published between 2016 and 2025 on non‑pharmacological interventions for chemotherapy‑related anxiety. Methods: A systematic search of PubMed, Scopus, Web of Science, and Google Scholar (January 2016–September 2025) identified RCTs and meta-analyses on non-pharmacological interventions for anxiety in adult cancer patients receiving chemotherapy or survivors. Non-randomized, pharmacological, and pediatric studies were excluded. Two reviewers independently extracted data on samples, interventions, outcomes, and effect sizes. RCT quality was assessed using Cochrane’s risk-of-bias tool. Results: Twenty-three studies (14 RCTs and nine reviews) met inclusion criteria, evaluating mindfulness-based stress reduction (MBSR), acceptance and commitment therapy (ACT), cognitive behavioral therapy (CBT), virtual reality (VR), music therapy, relaxation techniques, aromatherapy, gratitude or behavioral activation, Tai Chi/Qigong, hypnosis, acupuncture, and reflexology. MBSR showed the strongest effects, reducing distress (SMD = –1.35) and anxiety (SMD = –1.48) and improving self-efficacy. ACT and CBT achieved small-to-moderate anxiety reductions (SMD = –0.41 and –0.61). VR alleviated anxiety, pain, and stress, while music therapy alone or combined with relaxation significantly reduced anxiety and depression. Aromatherapy and gratitude-based interventions yielded modest benefits, whereas Tai Chi/Qigong (SMD = –0.99) and hypnosis improved anxiety. Guidelines recommend MBIs, yoga, hypnosis, relaxation, music, and lavender oil during treatment, and MBIs, yoga, acupuncture, Tai Chi/Qigong, and reflexology post-treatment. Conclusions: Non-pharmacological interventions offer promising adjuncts for chemotherapy-related anxiety. Strong evidence supports mindfulness-based therapies, ACT, CBT, VR, music therapy, relaxation, aromatherapy, and gratitude practices. Tai Chi/Qigong and hypnosis show emerging benefits, while evidence for reflexology and acupuncture remains limited. Integration should reflect patient preferences and resource availability. Future research needs standardized outcomes, larger trials, and combined approaches to strengthen evidence and optimize supportive care in oncology.